Conformational, spectroscopic, optical, physicochemical and molecular docking study of 4-methoxy-benzaldehyde oxime and 4-hydroxy-3-methoxy-benzaldehyde oxime. (2nd January 2020) - Kaya, Yunus; Kucuk, Ilhan; Kaya, Asli A.
ABSTRACT: In this study, the conformational, spectroscopic, optical, physicochemical and molecular docking studies of two oxime molecules, namely 4-methoxy-benzaldehyde oxime (mboH) and 4-hydroxy-3-methoxy-benzaldehyde oxime (hmboH) were reported. The conformational analyses and spectroscopic properties were performed by DFT/B3LYP method and 6–311++G(d, p) basis set to find the most probable geometries of both molecules. The optical properties, energy gap and nonlinear optical (NLO) properties were investigated in different solvents which are benzene, chloroform, ethanol, dimethyl sulfoxide (DMSO) and water. Some physicochemical properties were also performed. The stability of the mboH and hmboH arising from hyper-conjugative interaction and charge delocalisation has been analysed using natural bond orbital (NBO) analysis. The stability of the molecules arising from hyper conjugative interactions and charge delocalisation has been also analysed using NBO study. In addition, molecular docking studies with DNA and protein structures to find the most preferred binding mode of the ligands inside the DNA and protein cavity.